Partially Threaded Screws Require More Work During Removal Compared to Fully Threaded Screws in a Bone Simulation Model - Alexander J. Mayers, MD; Daniel Hayes, BS; Nathan Chaclas, MS3; Max Vogel, MD; Keith Grega, BS; Benjamin B. Wheatley, PhD; Mark Alan Seeley, MD (Elsevier, 2024)
ABSTRACT: Background: Routine slipped capital femoral epiphysis (SCFE) implant removal is controversial. Difficulty with hardware removal is well documented in SCFE patients, however, there is no biomechanical study demonstrating which specific aspect of screw morphology may be responsible for difficult removal. In this study, we compare the removal torques and work energy of fully and partially threaded cannulated SCFE screws from a bone simulation medium. Methods: 70 mm × 6.5 mm partially (20 mm threads) and fully threaded stainless-steel screws were tested by reversing them from a cured liquid resin medium. Peak torque and total work energy were recorded from a load cell apparatus during each trial. The mean peak torque and total work energy were compared between the partially threaded and fully threaded screw groups using Student's t-test. P < .05 was considered statistically significant. Results: The fully threaded screws (n = 20) had a mean peak torque of 10.59 Nm (standard deviation [SD] = 0.95 Nm), which was statistically significantly lower than the mean peak torque of the partially threaded screws (n = 23), 11.40 Nm (SD = 1.15 Nm) (P = .014). The fully threaded screws (n = 21) had a mean work of 598.7 J (SD = 208.3), which was statistically significantly lower than the mean work of the partially threaded screws (n = 23), 1,737.6 J (SD = 292.4 J) (P < .0001). Conclusions: Although our study did not perfectly model the in vivo "stuck screw phenomenon," our data demonstrate that partially threaded screws require more work of removal. Surgeons should consider the use of fully threaded screws if anticipating future hardware removal when selecting implants in the treatment of SCFE. Key Concepts: (1) Slipped capital femoral epiphysis hardware removal can be difficult, and construct selection can influence complication rates. (2) Removal torque differences exist between fully and partially threaded screws. (3) Partially threaded screws require greater work energy of removal in comparison to partially threaded screws. Level of Evidence: III